Examen al rubro inventarío/costo de venta de una empresa dedicada la producción y comercialización de radiadores comprendida entre el 1 de febrero del 2008 a marzo 31 del 2009 ubicada en la ciudad de Guayaquil - Mora Granda, Beverly Andrea (2009)
The present work focuses on an audit on the item Inventory / cost of Sale of a dedicated company the production and marketing of radiators understood (included) between February 1, 2008 on March 31 of 2009, the firs chapter theory’s the principal terms treated during the whole tesina. The second chapter is all related to the knowledge of the business. This chapter is important because are identified the processes, controls and risks that the studied company posses. After identifing the risks in a deep study one proceeded to realize the plan of audit and the tests (proofs) for each of the items to audit according to the materiality of planning. The third chapter is the audit of item in this one proceeds inventory / cost of Sale to implement the tests of audit and findings with a deep investigation(research) and information specifies collected by the company for the execution of the audit. In the fourth Chapter the findings are for each of the substantive tests of audit of the item to auditing and ultimately conclusions and general recommendations for the company.